Antimicrobial effect of Zingiber officinale var. officinale essential oil and nisin against pathogenic and spoilage microorganisms. (October 2019) - Ashari, D A; Nissa, A; Nursiwi, A; Sari, A M; Utami, R
Abstract: This study was conducted to investigate the antimicrobial effect of Zingiber officinale var. officinale essential oil (EO), nisin, and their combination against some pathogenic and spoilage microorganisms. Minimum Inhibitory Concentration (MIC), Minimum Bactericidal Concentration (MBC), Minimum Fungicidal Concentration (MFC) and the synergism effect were assayed. The MIC values of nisin on Aspergillus niger ; Eschericia coli and Pseudomonas fluorescens ; Bacillus cereus; and Salmonella typhimurium and Staphylococcus aureus were 250; 500; 2000; and >2000 IU, respectively. On the other hand, MIC values of EO on E. coli ; B. cereus and S. aureus ; Pseudomonas fluorescens and A. niger; and Salmonella typhimurium were 0, 125; 0.25; 0.5; and 4%, respectively. 62.5 IU of nisin combined with 2% of EO could inhibit the growth of Salmonella typhimurium, S. aureus, and E. coli. In addition, the combination of nisin and EO had synergistic effect against B. cereus, A. niger, and Salmonella typhimurium . The combination of nisin and EO had no bactericidal effect against all five bacterias but it had fungicidal effect against A. niger at concentration 62.5 IU of nisin and 1% of EO. Sabinene (16.88%), Z-citral (11.25%), and camphene (10.05%) were the major components in Zingiber officinale var. officinale EO which contributed on its antimicrobial activity.